MYCN is a novel oncogenic target in adult B‐ALL that activates the Wnt/β‐catenin pathway by suppressing DKK3. Issue 7 (19th April 2018) - Kong, Desheng; Zhao, Linlin; Sun, Lili; Fan, Shengjin; Li, Huibo; Zhao, Yanqiu; Guo, Zhibo; Lin, Leilei; Cui, Lin; Wang, Ke; Chen, Wenjia; Zhang, Yihui; et al.
Abstract: Dickkopf‐3 ( DKK3 ) is frequently down‐regulated by promoter hypermethylation and is closely associated with a poor prognosis in many cancers. Our previous studies have shown that miR‐708 down‐regulates DKK3 at the post‐transcriptional level in B‐ALL. However, whether transcriptional mechanisms lead to DKK3 silencing remains unclear. Here, we analysed the promoter regions of DKK3 by bioinformatics and found binding sites for MYCN. A dual‐luciferase reporter gene assay and ChIP experiments revealed that MYCN negatively regulates DKK3 at the transcriptional level in B‐ALL cell lines, and using bisulphite sequencing PCR, we affirmed that MYCN has no effect on the methylation of the DKK3 promoter. MYCN silencing in B‐ALL cells resulted in reduced cell proliferation, increased apoptosis and G1 phase arrest. Treatment with MYCN siRNA or 5‐aza‐2′‐deoxycytidine (5‐AdC), a demethylating agent, significantly increased the levels of DKK3 mRNA and protein and decreased the protein levels of p‐GSK3β and nuclear β‐catenin, which indicates inhibition of the Wnt/β‐catenin pathway in vitro. MYCN knockdown significantly decreased the tumorigenic capacity of Nalm6 cells, which restored DKK3 levels and inhibited the Wnt/β‐catenin pathway in vivo. Our study provides an increased understanding of adult B‐ALL pathogenesis, which may be beneficial to the development of effective prognostic markers or therapeutic targets.